Heterosis and gene action in bajra - napier hybrids - Serene M.Das (Department of Plant Breeding and Genetics, College of Agriculture, 2002)
A study on 'Heterosis and gene action in bajra-napier hybrids' was carried out with the objective of developing bajra-napier hybrids with high yield potential and good quality. The study was undertaken during the year 2001-2002 in the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani. Seven lines of bajra, viz., APFB-2, Composite 9, DRSB-3, FD 1917, HES-4, IP 15814 and TNSC-4 and three testers of napier grass, FD 431, FD 467 and FD 471 were crossed in a line x tester mating design to obtain 21 cross combinations. The hybrids were evaluated along with their parents for mean performance, combining ability, heterosis and gene action for eleven yield and yield related characters. Significant differences among treatments were observed for all the characters. Also significant differences among parents and crosses were observed for these characters and their general and specific combining ability variances and effects were studied. The magnitude of SCA variances alone was significant suggesting the predominance of non-additive gene action in controlling these traits. Based on mean performance and gea effects, HES-4 was identified as the best general combiner among lines followed by TNSC-4. Among testers, FD 467 can be selected as the best male parent followed by FD 471. The crosses, TNSC-4 x FD 471 and HES-4 x FD 467 were the promising combinations for green fodder yield and its component traits, based on mean performance, sea effects and standard heterosis. Hence these crosses can be exploited for developing high yielding hybrids.